A column evaluation of Appalachian coal mine spoils' temporal leaching behavior. (September 2015) - Orndorff, Zenah W.; Daniels, W. Lee; Zipper, Carl E.; Eick, Matt; Beck, Mike
Abstract: Appalachian surface coal mine overburden affects water quality as drainage percolates through spoil disposal fills. This study evaluated leaching potentials of 15 spoils from south-central Appalachia. Most bulk samples were non acid-forming, all were low in total-S, (≤0.34%), and initial saturated paste specific conductance (SC) ranged from 264 to 3560 μS cm −1 . Samples were leached unsaturated (40 cycles) and leachates analyzed for pH, SC, and ion composition. Overall, leachates from unweathered spoils were higher in pH and SC than leachates from weathered spoils. Fine-textured spoils generally produced higher SCs than more coarsely textured spoils. Mean SC for all spoils decreased rapidly from an initial peak of 1468 μS cm −1 (±150) to 247 μS cm −1 (±23). Release patterns for most major ions reflected declining SC. Bicarbonate typically increased with successive leaches, replacing sulfate as the dominant anion. Column SC values were comparable to relevant published field data. Highlights: Leaching potentials of diverse coal mine spoils were evaluated by column study. Column leachate was evaluated for pH, specific conductance, and ion composition. Degree of weathering impacted leachate pH, specific conductance, and ion release. Conductivity and most major ions decreased rapidly after first few leach events. Column leachate was consistent with relevant literature-based stream data. Abstract : Temporal response and ionic composition of total dissolved solids from Appalachian coal mine spoils was evaluated by column leaching and related to weathering and rock type.